1982
DOI: 10.1021/jm00346a012
|View full text |Cite
|
Sign up to set email alerts
|

Serotonin receptor affinity of cathinone and related analogs

Abstract: A series of cathinone (alpha-aminopropiophenone) analogues was examined using the isolated rat fundus preparation. (S)-(-)-Cathinone possesses twice the serotonin receptor affinity of (+/-)-cathinone and four times the affinity of racemic amphetamine. Several derivatives of cathinone were found to either possess a lower affinity than the parent compound or did not interact with the receptors in a competitive manner. Several novel analogues, 1-(aminomethyl)-3,4-dihydronaphthalene hydrochloride (3), 4-(aminometh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

1982
1982
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(21 citation statements)
references
References 2 publications
2
19
0
Order By: Relevance
“…however, indications in the literature that interaction with serotoninergic neurons might be a quite important aspect in the overall effect of the khat alkaloid. Thus, it has been reported that (-)-cathinone decreases the ability of cats to differentiate between visual stimuli, and that this decrease does not occur when the animals are pre treated with either the serotonin synthesis blocker pchlorphenylalanine or the serotonin receptor antagonist methysergide [14], Furthermore, by using a two-lever drug discrimination procedure it was found that rats trained with the serotonin agonist quipazine were less likely to distinguish between (-)-cathinone and quipazine than between (+)-amphetamine and quipa/ine [15], This observation correlates with results indicating that the affinity of (-)-cathinone for rat fundus serotonin recep tors is four times higher than that of racemic amphet amine [16], It is possible, therefore, that due to higher activity at postsynaptic sites, (-)-cathinone has a gener ally more pronounced effect on serotoninergic neuro transmission than (+)-amphetamine, and it would be of interest to investigate this further. With regard to release from serotonin storage sites, however, (-)-cathinone ap pears to have no greater specificity than (-^-amphet amine.…”
Section: Discussionsupporting
confidence: 57%
“…however, indications in the literature that interaction with serotoninergic neurons might be a quite important aspect in the overall effect of the khat alkaloid. Thus, it has been reported that (-)-cathinone decreases the ability of cats to differentiate between visual stimuli, and that this decrease does not occur when the animals are pre treated with either the serotonin synthesis blocker pchlorphenylalanine or the serotonin receptor antagonist methysergide [14], Furthermore, by using a two-lever drug discrimination procedure it was found that rats trained with the serotonin agonist quipazine were less likely to distinguish between (-)-cathinone and quipazine than between (+)-amphetamine and quipa/ine [15], This observation correlates with results indicating that the affinity of (-)-cathinone for rat fundus serotonin recep tors is four times higher than that of racemic amphet amine [16], It is possible, therefore, that due to higher activity at postsynaptic sites, (-)-cathinone has a gener ally more pronounced effect on serotoninergic neuro transmission than (+)-amphetamine, and it would be of interest to investigate this further. With regard to release from serotonin storage sites, however, (-)-cathinone ap pears to have no greater specificity than (-^-amphet amine.…”
Section: Discussionsupporting
confidence: 57%
“…In vitro studies, for instance, have shown that cathinone enhances the release of serotonin from the striatum [70,71] and can bind to serotonin receptors [72] . A study by Fleckenstein et al [73] demonstrated serotonin uptake inhibition by cathinone following single or multiple dosing.…”
Section: Khat and Monoaminesmentioning
confidence: 99%
“…Like amphetamine, cathinone induces release of dopamine, serotonin (5-hydroxytryptamine, 5-HT) and noradrenaline from pre-synaptic neuronal terminals, and has further been suggested to inhibit neurotransmitter reuptake [3]. Cathinone, cathine and norephedrine have been shown to act as substrates at the noradrenaline and dopamine transporters, to bind α 2 -adrenergic receptors [9,10], and cathinone has in addition been reported to bind 5-HT receptors [10,11]. The β 1 -adrenergic receptor was suggested to mediate khat-induced increase in systolic blood pressure and pulse rate [12], whereas the α 1 -adrenergic receptor has been implicated in bladder dysfunction following khat chewing [13].…”
Section: Introductionmentioning
confidence: 99%